Age at menarche and current substance use among Canadian adolescent girls: results of a cross-sectional study - Al-Sahab Ban; Ardern Chris I; Hamadeh Mazen J; Tamim Hala (BMC, 2012)
Abstract Background Substance use is among the key public health threats that find its genesis during adolescence. Timing of puberty has been lately researched as a potential predictor of subsequent substance abuse. The present study, therefore, aims to assess the effect of age at menarche on current practices of smoking, alcohol drinking and drug use among 14-15 year old Canadian girls. Methods The analysis of the study was based on all female respondents aged 14 to 15 years during Cycle 4 (2000/2001) of the National Longitudinal Survey of Children & Youth (NLSCY). The main independent variable was age at menarche assessed as the month and year of the occurrence of the first menstrual cycle. The dependent variables were current smoking, heavy alcohol drinking in the past 12 months and drug use in the past 12 months. Three logistic regression models were performed to investigate the association between age at menarche and each of the substance use outcomes, adjusting for possible confounders. Bootstrapping was performed to account for the complex sampling design. Results The total weighted sample included in the analysis represented 295,042 Canadian girls. The prevalence of current smokers, heavy drinkers (drunk in the past 12 months) and drug users in the past 12 months was approximately 22%, 38% and 26%, respectively. After adjusting of all potential confounders, no association was found between age at menarche and any of the substance use outcomes. School performance and relationship with the father, however, stood out as the main variables to be associated with smoking, heavy drinking and drug use. Conclusions Qualitative studies understanding the social and psychological changes experienced by early maturing Canadian adolescents are warranted to identify other correlates or pathways to substance use in this higher risk population.